Construction of the Reagent Panel “GenPest-subspecies/Altai-RGF” - K. A. Nikiforov; L. M. Kukleva; D. A. Sitmbetov; N. A. Osina; G. A. Eroshenko; V. V. Kutyrev (Проблемы особо опасных инфекций, 2022)
The aim of the study was to develop a test system that allows for detecting plague pathogen DNA in clinical and biological samples, environmental objects with the simultaneous determination of its appurtenance to the main and non-main subspecies, differentiation of the altai biovar central asiatica subspecies separately. Materials and methods. Primer sets for specific genetic markers have been selected using the VectorNTI 10 software, optimal conditions for PCR were determined for RotorGene devices. To assess the specificity and sensitivity of the developed set of reagents, 44 strains of microorganisms were used, of which 19 were Yersinia pestis strains and 25 strains of heterologous microorganisms. The diagnostic sensitivity of “GenPest-subspecies/Altai-RGF” is 98.6 % with a confidence level of probability of 91 %. The diagnostic specificity of “GenPest-subspecies/Altai-RGF” is ≥ 99 % with a confidence level of 91 %. Results and discussion. A medical product “A set of reagents for the detection and differentiation of plague pathogen strains of the main and non-main subspecies (altai biovar, subspecies central asiatica exclusively) by the polymerase chain reaction with hybridization-fluorescent registration of results in real-time mode (GenPest-subspecies/Altai-RGF)” has been developed. The set of reagents passed the state registration in accordance with the established procedure. The use of the developed set of reagents is relevant for the Gorno-Altai high-mountain plague focus of the Russian Federation and the adjacent part of Mongolia.